Hiv prevention research among severely mentally ill latinas: an examination of ethical issues in the context of gender and culture - Loue, Sana (Acta Bioethica, 2007)
We examine the interplay between ethical issues, gender, and culture in the context of our study which examines the context of HIV risk among Puerto Rican and Mexican women with schizophrenia, bipolar disorder, and major depression. Culture and gender are considered in the evaluation of ethical questions related to scientific issues reseach team issues, analysis of risks and benefits of participating, confidentiality of data and privacy of the study participants, selection and recruitment, informed consent and decisional capacity, incentives, institutional and peer review matters, data presentation, and community needs. Ethical obligations to research participants and the relevant community are discussed.